Benign Prostate Hyperplasia (BPH) – Induced Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH): A Rare Precipitant of Acute Decompensated Heart Failure - Wahyu Aditya; Bunga Dewanggi; Paskariatne Probo Dewi; Teuku Muhammad Haykal Putra; Hawani Sasmaya Prameswari (The Indonesian Heart Association, 2026)
In Acute decompensation of heart failure (ADHF), the precipitating factors need to be identified and treated promptly. Urinary retention is rarely recognized as a cause of ADHF. Here, we presented a case of Benign Prostate Hypertrophy (BPH) with urinary retention inducing SIADH, which precipitated an episode of decompensated heart failure. The correction of hyponatremia and placement of a DC catheter, along with diuretic and tolvaptan administration, dramatically improved the patient’s condition.